Penerapan Program ODOJ (One Day One Juz) dalam Upaya Peningkatan Minat dan Kemampuan Membaca Al-Quran pada Anak di Perumahan Jatiwangi - Zohro, Nailul Padhil; Putro, Khamim Zarkasih; Munastiwi, Erni; Akip, Muhammad (STAI Bumi Silampari, 2023)
Allah revealed the Qur’an as the holy book of Muslims SWT to the prophet Muhammad through the angel Gabriel which is used as a guide for human life. namely By reading the Qur'an regularly, Allah has promised a double reward for people who are always close to the Qur'an. Sometimes there are many Muslims who do not know the importance of reading the Qur'an apart from getting a reward as well as a cure for all problems. This study aims to find out how much interest children have in reading the Qur'an and how to add motivation to children in reading the Qur'an. Because sometimes humans need motivation or encouragement to be istiqomah in doing good. This is where the ODOJ community plays an important role in building the motivation of its members. As Muslims we are obliged to carry out the commands of Allah SWT. Starting from the habit of reciting the Koran which decreased during Ramadan among Muslims and less and less interacting with the Qur’an due to increased busyness and routine. In order to obtain relevant and quality data and explanations in this scientific work, the author uses a form of Islamic education approach which is very useful for discovering the nature and meaning contained in the educational process itself and the data is obtained from the field where the educational process takes place in the context of its environment. Data collection techniques were carried out through observation, interviews and documentation. The method that the author uses in analyzing the data obtained is by using the methods of data collection, data reduction, data presentation, data verification and drawing conclusions. This study concludes that the application of the ODOJ (One Day One Juz) program is very helpful in increasing the interest and ability to read the Koran in children. With the ODOJ program, children have the responsibility to finish reading the Qur’an regularly so that teenagers will automatically take the time to read the Qur’an.